χ2 Attacks on Block-Cipher based Compression Functions - Freitas, Daniel Santana de; Nakahara Jr, Jorge (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2012: Anais do XII Simpósio Brasileiro de Segurança da Informação e de Sistemas Computacionais, 2012)
In this paper, we report on χ2 analyses of block-cipher based (cryptographic) compression functions. Our aim is not to find collisions nor (second) preimages, but to detect non-random properties that may distinguish a compression function from an ideal primitive such as a random oracle. We study some well-known single-block modes of operation such as Davies-Meyer (DM), Matyas-Meyer-Oseas (MMO) and Miyaguchi-Preneel (MP), and double-block modes such as Hirose's, Tandem-DM, Abreast-DM, Parallel-DM and MDC-2. This paper shows how a weakness (χ2 correlation) in the underlying block cipher can propagate to the compression function via the mode of operation used in hash constructions. To demonstrate our ideas, we instantiated the block cipher underlying these modes with variable-round RC5, RC6 and ERC6 block ciphers.